Moving closer or drifting apart: Distributional effects on monetary policy - Lucas Hafemann; Paul Rudel; Jörg Schmidt (Philipps-University Marburg, School of Business and Economics, 2017)
Our paper picks up the current controversial debate about increasing (income) inequality due to recent monetary policy measures in major advanced economies. We use a VAR framework identified with sign restrictions to figure out how income in- equality related measures react to monetary policy shocks in three different advanced economies with an independent monetary policy regime. We choose the U.S., Canada and Norway. While all economies experience an increase in Gini coefficients of market income in the presence of an expansionary monetary policy shock, only the U.S. and Canada show a significant response in the Gini coefficient of disposable income when facing such shocks. To figure out how the transmission of monetary policy to overall income inequality works we pick up two major channels dominant in literature: The employment channel and the income composition channel. The latter is analyzed by data from national accounts concerning two different kinds of income households receive: Labor related income and capital payments, both net. We find that while in the U.S. as well as in Canada capital income recipients profit disproportionately from expansionary monetary policy, in Norway both types of (net) income benefit similarly from expansionary monetary policy shocks. We conclude that fiscal policy makers can successfully address and mitigate harmful effects of increased market income inequality.
Keywords: D31; D33; E24; E25; E52; E64; 330; Income Inequality; Factor Income Distribution; Monetary Policy; VAR; Sign-Restrictions